A bioethical and comprehensive approach to obesity towards human dignity and happiness - Serrano-Plata, María de Jesús (2025)
Obesity is a complex and multifactorial public health problem that requires immediate attention through the redress of the social and structural determinants and social injustices that contribute to its development. The objective of this research is to propose a comprehensive bioethical approach to obesity that fosters human dignity and happiness, based on the experiences of people with excess body fat. This qualitative, descriptive study explored the experiences of people living with obesity who successfully completed the SIN MEDIDA program. Responses were categorized using the principles of thematic analysis. A total of 12 people from different socioeconomic levels recognized that programs aimed at this population group should promote learning and enjoyment, as well as provide psychological, physical, and social benefits with professional support. It is imperative that programs pursue a bioethical approach that initiates strong informed consent and is oriented toward human dignity. More importantly, it is imperative that treatments, interventions, and recommendations for people living with obesity guarantee their long-term happiness.